Effect of Ursodeoxycholic Acid Alone Verses Ursodeoxycholic Acid and Rifampicin in Obstetric Cholestasis - Ayesha Amjad; Sadia Aftab; Tahreem Sehar; Samana Haider; Tehmina Aziz Qureshi; Kainaat Kanwal (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Intrahepatic cholestasis of pregnancy (ICP) is a common liver disorder in pregnancy, associated with pruritus, elevated bile acids, and increased risk of adverse perinatal outcomes. While Ursodeoxycholic Acid (UDCA) is the first-line treatment, some patients respond inadequately. This study aimed to compare the effectiveness of UDCA alone versus UDCA combined with Rifampicin in reducing clinical symptoms and improving biochemical markers in women with ICP.